Injury to thalamocortical projections following traumatic brain injury results in attractor dynamics for cortical networks. (March 2022) - Mofakham, Sima; Liu, Yuhao; Hensley, Asher; Saadon, Jordan R.; Gammel, Theresa; Cosgrove, Megan E.; Adachi, Joseph; Mohammad, Selma; Huang, Chuan; Djurić, Petar M.; Mikell, Charles B.
Highlights: Consciousness is associated with complex cortical activity. Injury to thalamo-prefrontal connections leads to cortical attractor dynamics. This attractor generates deterministic and predictable cortical activity. The number of available cortical states in this attractor regime is limited. Thalamic input is critical to cortical flexibility required for consciousness. Abstract: Major theories of consciousness predict that complex electroencephalographic (EEG) activity is required for consciousness, yet it is not clear how such activity arises in the corticothalamic system. The thalamus is well-known to control cortical excitability via interlaminar projections, but whether thalamic input is needed for complexity is not known. We hypothesized that the thalamus facilitates complex activity by adjusting synaptic connectivity, thereby increasing the availability of different configurations of cortical neurons (cortical "states"), as well as the probability of state transitions. To test this hypothesis, we characterized EEG activity from prefrontal cortex (PFC) in traumatic brain injury (TBI) patients with and without injuries to thalamocortical projections, measured with diffusion tensor imaging (DTI). We found that injury to thalamic projections (especially from the mediodorsal thalamus) was strongly associated with unconsciousness and delta-band EEG activity. Using advanced signal processing techniques, we found that lack of thalamic input led to 1.) attractor dynamics for cortical networks with a tendency to visit the same states, 2.) a reduced repertoire of possible states, and 3.) high predictability of transitions between states. These results imply that complex PFC activity associated with consciousness depends on thalamic input. Our model implies that restoration of cortical connectivity is a critical function of the thalamus after brain injury. We draw a critical connection between thalamic input and complex cortical activity associated with consciousness.